'Abagyenda bareeba. Those who Travel, See': Home, Migration and the Maternal Bond in Doreen Baingana's Tropical Fish. Issue 2 (3rd May 2016) - Gichanda Spencer, Lynda
ABSTRACT: Doreen Baingana's Tropical Fish explores the migratory experiences of the main narrator-focalizer, Christine Mugisha, as she travels from Uganda to the United States of America. Although the analyses of home, exile, and migration by writers like Edward Said and Paul Tiyambe Zeleza tend to be ungendered; Baingana seems to elaborate on these concerns by reflecting on the gendered experience of travel. As Carole Boyce Davies has argued, the act of travelling and migration opens up new spaces and possibilities for black women writers as they come into contact with multiple places and cultures. In their encounters with migration, black women are able to negotiate and re-negotiate their identities. This article focuses on how Tropical Fish, interrogates complex, contradictory, ambiguous and often conflicted questions of home and migration with their concomitant issues of belonging and alienation/ estrangement and how they are intimately tied to the maternal bond. The article argues that Tropical Fish theorises the gendering of travel by trying to think through the mother-daughter relationship in terms of the daughter who abandons the home and how her diverse experiences of travel and migration contribute to the formation of an individual sense of self. In other words, it enables us to ask, why do the daughters travel; what difference does it make when daughters travel; what happens when the daughter returns to the mother ; when the mother speaks to the returning daughter?